Baltic journal of management : qualitative research: opportunities for researchers in the Baltic region - Cassell, Catherine; Symon, Gillian (Opportunities for researchers in the Baltic region: Volume 10, Issue 2., 2015)
This e-book is dedicated to looking at qualitative research methods in the Baltic region. This area has experienced rapid economic and political change and qualitative research methods can create original and perceptive methods and frameworks for addressing these challenges.